On-treatment comparison between corrective His bundle pacing and biventricular pacing for cardiac resynchronization: A secondary analysis of the His-SYNC Pilot Trial - Upadhyay, Gaurav A.; Vijayaraman, Pugazhendhi; Nayak, Hemal M.; Verma, Nishant; Dandamudi, Gopi; Sharma, Parikshit S.; Saleem, Moeen; Mandrola, John; Genovese, Davide; Oren, Jess W.; Subzposh, Faiz A.; Aziz, Zaid; et al. (Heart rhythm, 2019)
The His-SYNC pilot trial was the first randomized comparison between His bundle pacing in lieu of a left ventricular lead for cardiac resynchronization therapy (His-CRT) and biventricular pacing (BiV-CRT), but was limited by high rates of crossover. To evaluate the results of the His-SYNC pilot trial utilizing treatment-received (TR) and per-protocol (PP) analyses. The His-SYNC pilot was a multicenter, prospective, single-blinded, randomized, controlled trial comparing His-CRT vs BiV-CRT in patients meeting standard indications for CRT (eg, NYHA II–IV patients with QRS >120 ms). Crossovers were required based on prespecified criteria. The primary endpoints analyzed included improvement in QRS duration, left ventricular ejection fraction (LVEF), and freedom from cardiovascular (CV) hospitalization and mortality. Among 41 patients enrolled (aged 64 ± 13 years, 38% female, LVEF 28%, QRS 168 ± 18 ms), 21 were randomized to His-CRT and 20 to BiV-CRT. Crossover occurred in 48% of His-CRT and 26% of BiV-CRT. The most common reason for crossover from His-CRT was inability to correct QRS owing to nonspecific intraventricular conduction delay (n = 5). Patients treated with His-CRT demonstrated greater QRS narrowing compared to BiV (125 ± 22 ms vs 164 ± 25 ms [TR], P < .001;124 ± 19 ms vs 162 ± 24 ms [PP], P < .001). A trend toward higher echocardiographic response was also observed (80 vs 57% [TR], P = .14; 91% vs 54% [PP], P = .078). No significant differences in CV hospitalization or mortality were observed. Patients receiving His-CRT on-treatment demonstrated superior electrical resynchronization and a trend toward higher echocardiographic response than BiV-CRT. Larger prospective studies may be justifiable with refinements in patient selection and implantation techniques to minimize crossovers. [Display omitted]